How are pay-for-performance schemes in healthcare designed in low- and middle-income countries? Typology and systematic literature review - Kovacs, Roxanne J.; Powell-Jackson, Timothy; Kristensen, Søren R.; Singh, Neha; Borghi, Josephine (BMC health services research, 2020)
Background Pay for performance (P4P) schemes provide financial incentives to health workers or facilities based on the achievement of pre-specified performance targets and have been widely implemented in health systems across low and middle-income countries (LMICs). The growing evidence base on P4P highlights that (i) there is substantial variation in the effect of P4P schemes on outcomes and (ii) there appears to be heterogeneity in incentive design. Even though scheme design is likely a key determinant of scheme effectiveness, we currently lack systematic evidence on how P4P schemes are designed in LMICs. Methods We develop a typology to classify the design of P4P schemes in LMICs, which highlights different design features that are a priori likely to affect the behaviour of incentivised actors. We then use results from a systematic literature review to classify and describe the design of P4P schemes that have been evaluated in LMICs. To capture academic publications, Medline, Embase, and EconLit databases were searched. To include relevant grey literature, Google Scholar, Emerald Insight, and websites of the World Bank, WHO, Cordaid, Norad, DfID, USAID and PEPFAR were searched. Results We identify 41 different P4P schemes implemented in 29 LMICs. We find that there is substantial heterogeneity in the design of P4P schemes in LMICs and pinpoint precisely how scheme design varies across settings. Our results also highlight that incentive design is not adequately being reported on in the literature – with many studies failing to report key design features. Conclusions We encourage authors to make a greater effort to report information on P4P scheme design in the future and suggest using the typology laid out in this paper as a starting point.